A comparison between a natural gas power plant and a municipal solid waste incineration power plant based on an emergy analysis. (20th November 2020) - Yazdani, Shima; Salimipour, Erfan; Moghaddam, Mojtaba Saei
Abstract: This paper performs an emergy analysis (EmA) to compare two real power plants include a conventional natural gas steam power plant (NGPP) with one that burns municipal solid waste (MSWPP). For this purpose, the EmA is used to investigate the sustainability, renewability, environmental impacts, and economic issues. The capacity of the NGPP and MSWPP are 247.5 and 3 MW, respectively. Results from this study show that the percent of renewability (PR) and emergy sustainability index (ESI) of the MSWPP are much more than those of the NGPP. The PR and ESI of the MSWPP are 46.81 and 1.65, while for the NGPP are 5.01 and 0.05, respectively. It is proved that the MSWPP is more efficient and has the better environmental impacts compared to the NGPP. Moreover, a hypothetical MSWPP with the same electricity output of the NGPP is studied using the EmA. A more efficient system with the higher PR and ESI is observed compared to the other case studies. Beside of these advantages, use of the MSW has other benefits such as reducing the greenhouse gases released in the atmosphere, saving fossil fuels, low land area required compared to the landfill, speed and ease of disposal, and production of clean and useful ash. Highlights: Emergy analysis is used to compare two kind of power plants. The fuels of one of the power plants is natural gas and the other is MSW. The emergy indices (EYR, ELR, and ESI) have been computed to compare them. The best ESI is obtained by using the MSW as a fuel in power plants.